Influence of the refractories chemical composition onto opal glass furnace durability - Khoruzhenko, Olena; Lykhyi, Vladyslav (Lviv Polytechnic Publishing House, 2016)
In this paper, study of refractories corrosion processes at a basic production stage of an opal glass were described. Main problem of the glass furnaces for opal glass is unability to use high-zirconia oxide lining because of fragility such refractories, caused by transition of zirconium oxide crystals from monocline crystal system to cubic crystal system. There was found the optimal chemical composition for such purposes, based on Zirconia Aluminum Silicates which may increase the term of service of furnaces.
Keywords: opal glass; fluorine; corrosion; refractories; lining; glass production; aluminium zirconia silicates